Analisis Pengaruh Influencer Marketing terhadap Brand Awareness dan Purchase Decision pada Produk The Originote - Putri Rohmawati, Shintya; Arqy Ahmadi, Mirzam (Teewan Journal Solutions, 2025)
In recent years, influencer marketing has become one of the most effective marketing strategies, especially in the digital era marked by the rapid development of social media. Many companies, including The Originote, utilize influencer marketing to increase brand visibility and influence consumer behavior. This study focuses on analyzing the influence of influencer marketing on brand image, brand awareness, brand trust, and purchasing decisions for skincare products. Through a combination of qualitative and quantitative approaches, data was collected from active skincare product users on social media. The results show that influencer marketing has a positive impact on brand image, which further strengthens brand awareness among consumers. Brand trust built by influencers also contributes to purchasing decisions, although other factors such as price and product quality also influence. This study emphasizes the importance of choosing influencers who are in line with the brand identity to form positive and consistent associations.